Medical waste management-related factors affecting health and experiences of health risks among medical waste handlers in low and middle-income countries: a systematic review protocol of qualitative studies - Tewodros Getachew Hailemariam; Setho Hadisuyatmana; Rakibul M Islam; Andre M N Renzaho; Md Nazmul Huda; Syeda Zakia Hossain; James Sujit Malo; Sajedul Khan; Afsana Ferdous; Blessing Akombi-Inyang (BMJ Open)
Introduction Medical waste management (MWM)-related factors affecting the health of medical waste handlers (MWHs) and their health risks in low and middle-income countries (LMICs) are an important public health concern. Although studies of MWM-related factors and health risks among MWHs in LMICs are available, literature remains undersynthesised and knowledge fragmented. This systematic review will provide a comprehensive synthesis of evidence regarding the individual, system and policy-level MWM-related factors that affect MWHs’ health and their experiences of health risks in LMICs.Methods and analysis All qualitative studies published in peer-reviewed journals between 1 July 2011 and 30 June 2021 with full texts available and accessible will be included in the review. Seven specific electronic databases (eg, Scopus, Ovid MEDLINE, EMBASE, Global Health, CINAHL, ProQuest and PsycINFO) will be searched. Two authors will review the citations and full texts, extract data and complete the quality appraisal independently. A third reviewer will check discrepancies when a consensus cannot be reached on differences between the two reviewers. Data extraction will be conducted using the Joanna Briggs Institute standardised data extraction form for qualitative research. The quality of articles will be assessed using a Critical Appraisal Skills Programme checklist. Results from eligible articles will be synthesised into a set of findings using the thematic framework analysis approach and will be reported according to the Enhancing Transparency in Reporting the Synthesis of Qualitative Research statement.Ethics and dissemination This review is based on published articles, which does not require ethical approval because there is no collection of primary data. Findings from this review will be published in a peer-reviewed journal and presented at relevant public health conferences. This protocol has been registered with the International Prospective Register of Systematic Reviews (PROSPERO).PROSPERO registration number CRD42020226851.